Figurative Language Found in Selected Song Lyrics by Eminem - Muhammad Faiz Kholilullah (P-SEMART JOURNAL, 2021)
Figurative language is an additional way of saying something than using the usual one. Thus, there are figurative words or phrases that cannot be literally true in any circumstances. This study discusses about an analysis of figurative language in Mockingbird by Eminem. The purpose of this study is to find the type of figurative language used and the contextual meaning in Mockingbird by Eminem. The source of the data was taken from the lyrics of Mockingbird by Eminem. Mockingbird by Eminem is classified as rap song released on November 12th, 2004. The research design used in this study is descriptive qualitative research with a document or content analysis as the research type. The thesis described type of figurative language and contextual meaning from Mockingbird by Eminem. From the analysis, there were nine types of figurative languages: they were metaphor, simile, symbol, personification, metonymy, allegory, hyperbole, and irony. To support the analysis, some types of figurative language and other related references were used. There were also some related theories about figurative language used to support the analysis. Twenty five have been selected to be analyzed. There were 2 types of Metaphor, 5 types of Simile, 3 types of Symbol, 1 type of Personification, 4 types of Metonymy, 1 type of Allegory, 6 types of Hyperbole, and 3 types of Irony. Then the types of figurative language were classified and analyzed. This study is highly expected to give contribution for the reader to know about figurative language clearly. It can help the reader know contextual meaning and enrich new English vocabulary used in the daily conversation. It is also can be expected to speak English fluently.